Making the Case for Research on Disease-Modifying Treatments to Tackle Post-lingual Progressive Sensorineural Hearing Loss - Van Rompaey, Vincent (Frontiers in Neurology, 2020)
Hearing loss not only has a significant impact on the quality of life of patients and society, but its correlation with cognitive decline in an aging population will also increase the risk of incident dementia. While current management of hearing loss is focused on hearing rehabilitation (and essentially symptomatic), patients are suffering from the burden of progressive hearing loss before hearing aids or cochlear implants are fitted. Although these devices have a significant effect on speech understanding, they do not always lead to normal speech understanding, especially in noisy environments. A significant number of patients suffer from autosomal dominantly inherited disorders that can produce progressive sensorineural hearing loss. This includes DFNA9, a disorder caused by pathologic variants in the COCH gene that leads to post-lingual profound sensorineural hearing loss and bilateral vestibulopathy. Carriers of a pathogenic variant leading to DFNA9 can be diagnosed at the pre-symptomatic or early symptomatic stage which creates a window of opportunity for treatment. Preventing hearing loss from occurring or stabilizing progression would provide the opportunity to avoid hearing aids or cochlear implants and would be able to reduce the increased incidence of dementia. While innovative therapies for restoration of hearing have been studied in case of severe-to-profound sensorineural hearing loss and congenital hearing loss, further research is needed to study how we can modify disease progression in late-onset autosomal dominant hereditary sensorineural hearing loss. Recently, gene editing strategies have been explored in autosomal dominant disorders to disrupt dominant mutations selectively without affecting wild-type alleles.